Malonate induces the assembly of cytoplasmic stress granules. Issue 1 (8th January 2016) - Fu, Xue; Gao, Xingjie; Ge, Lin; Cui, Xiaoteng; Su, Chao; Yang, Wendong; Sun, Xiaoming; Zhang, Wei; Yao, Zhi; Yang, Xi; Yang, Jie
Abstract : Malonate, a classic inhibitor of respiratory electron transport chain, induces mitochondrial stress. Stress granules (SGs) are a kind of dynamic foci structure during stress. The study on the connection of mitochondrial stress and SG assembly is still limited. Here, we demonstrated that malonate treatment leads to SG formation and translation inhibition, apart from mitochondrial stress, including enhanced ROS formation, reduced mitochondrial Δψm and ATP level. The phosphorylation levels of eIF2α and 4EBP1 protein were affected upon mitochondrial dysfunction. However, knockdown of 4EBP1 affected SG formation, rather than eIF2α. In addition, an increase of ATP level under mitochondrial stress enhanced malonate‐induced SG aggregation. Overall, malonate stimulation triggers mitochondrial stress and induces the assembly of non‐canonical cellular SGs via 4EBP1 pathway. Abstract :